Implementation And Evaluation Of The Bilingual Program For Eighth-Grade Students At MTSN 1 Sidrap - Rengko HR, Sumarlin; Hermansyah, Sam (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
This study investigates the implementation and evaluation of the bilingual program for eighth-grade students at Madrasah Tsanawiyah Negeri 1 Sidrap (MTSN). As globalization intensifies, bilingual education is becoming increasingly vital in preparing students for future academic and professional challenges. This research focuses on how the bilingual program is integrated into the curriculum at MTSN, with particular emphasis on its effectiveness in enhancing students' proficiency in both Indonesian and English.The study employs a mixed-methods approach to evaluate the program's impact. Quantitative data were collected through standardized language proficiency tests and academic performance records, while qualitative insights were gathered from interviews with educators, students, and parents. The research aims to assess the program's success in improving language skills, examine any challenges encountered during implementation, and provide recommendations for program enhancement. Preliminary findings suggest that the bilingual program has positively impacted students' language proficiency and academic performance. However, challenges such as insufficient teacher training and resource limitations were identified. The study underscores the importance of continuous evaluation and adaptation to address these challenges and enhance the program's effectiveness.This research contributes to the broader discourse on bilingual education by providing empirical evidence on the implementation and impact of bilingual programs in a specific educational context. The insights gained from this study are expected to inform policy decisions and practice in bilingual education, particularly in similar educational settings.